Was Patrick Influenced by the Teaching of Pelagius? - Bonner, Alison (The journal of theological studies, 2012)
Patrick’s Confessio and Epistola ad milites Corotici are the only surviving texts written by a British author in the fifth century which offer first-hand evidence about the nature of Christianity in Britain and Ireland at that time; for this reason a careful assessment of the information that they contain is important. The fifth century saw controversy among Christians over the relationship between divine grace and human free will. Two fifth-century Gallic authors described how the British church was disturbed by this debate. If this was true, then we might expect Patrick to address the subject in some way, and in this essay I explore whether the controversy is reflected in Patrick’s writings. For much of the twentieth century scholarship emphasized the poor quality of Patrick’s Latin and accepted Patrick’s description of himself as ‘unlearned’. I examine the doctrinal content of Patrick’s writings on the issue of grace and free will in order to discover whether he was familiar with the theological argument, and seek to place his works within a nuanced account of the fifth-century theological context. Hanging over the study of Britain in the early Middle Ages is a question about the causes of the exceptional monastic fervour that characterized Insular Christianity; this essay contributes to establishing a context that may enable this question to be answered.